The methodology of assigning the reliability index β to determine the safety of structural steel constructions at all operational phases - Kolesnichenko, S.; Selyutyn, Y.; Chernykh, I.; Mnacakanyn, K. (Ways to Improve Construction Efficiency, 2020)
In order to assess the operational safety of steel constructions, the paper analyzes the principles of calculating the safety of structural steel constructions with consideration for the reliability index β at all phases of constructions operation and the design fundamentals of the reliability index β for both new constructions (at the design stage) and structural steel constructions in the conditions of the long-term operation. The task of safety and reliability calculations, first of all, consists in assigning normalized safety parameter values, i.e. normalizing the reliability index, the value of which should be strictly related to the consequence classes (CC), which are determining for setting the reliability coefficients for further calculations while designing the constructions. The article considers the calculation values β of the reliability index for constructions operated beyond the time limit for operation, with accumulated defects and damages. To improve the mechanism for calculating the reliability index value for the constructions operated beyond the maximum operating limit, with accumulated defects and damages, several tasks were set to determine such values β of the reliability index below which the construction is no longer considered to be operational and to define the reliability index values β for possible performance of renovation works (reconstruction, refurbishment) to strengthen and extend the remaining structural lifetime. Thus, emphasizing all of the aforementioned, the main conclusions to the article should be specified: at the stage of solving the issue of calculating the reliability index for structures being operated over the projected service life, with damages and initial defects accumulated during the operation period, it is required to perform their review and determine two main criteria for solving the issue of determining the reliability index, namely: to set such values of the reliability index below which the structure will be no longer operational, to define and set such values of the reliability index at which it is possible to carry out renovation works on steel structures, their reconstruction or repair. Considering the possibility of changing the reliability index compared to a new structure, given that the residual service life may be shorter than the design one, taking into account the economic factors and factors of probability of losing a person’s life, setting of such reliability index values is necessary for further possibility of the service life extension of a structure and determination of its residual life.